Bruegel według Majewskiego. Literackie i malarskie problemy adaptacji - Wysłouch, Seweryna (Przestrzenie Teorii, 2023)
Lech Majewski’s The Mill and the Cross (2011) is a full-length feature film, a screen adaptation of Pieter Bruegel’s painting The Way of the Cross (1564). Majewski proves to be an excellent interpreter of Bruegel’s art, whom he considers a philosopher, an epic, and a poet. He relies on the research of Michael F. Gibson, and in his plotting he draws on a long-standing tradition of literary experience and digital technology (without this, it would have been impossible to faithfully reproduce the overall plan and realities of the painting). Majewski exposes the palimpsest nature of the narrative and shapes the film like a contemporary novel of space. In order to make the ideas of the screened painting comprehensible and to emphasize the fictionality of the depicted world, he introduces various versions of “literature about literature”. In the film, he perfectly integrates painterly features (word reduction, stop motion, long static camera shots) and literary features (the structure of an episodic novel of manners).